1998
DOI: 10.1177/002221949803100304
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Language Learning Difficulties

Abstract: For 10 years, the authors of this article have examined cognitive, affective, and linguistic influences on foreign language learning. They have proposed the Linguistic Coding Differences Hypothesis (LCDH) as a model for understanding foreign language learning problems. The authors review their empirical support for the LCDH and explain the diagnostic, pedagogical, and policy implications of their research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
66
0
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 52 publications
(50 reference statements)
13
66
0
6
Order By: Relevance
“…In other words, the skills one from language are transferred to the other, the person with more L1 practice thus being better at transferring these skills to the other language. They also support Ganschow, Sparks et al's thesis (Ganschow et al, 1992;Sparks et al, 1992;Ganschow, Sparks, & Javorsky, 1998;Sparks, Ganschow, & Javorsky, 2000) that phonological, orthographical, grammatical, and semantic L1 skills form the basis for learning L2. These authors found that students who find learning L2 difficult have low-level learning disabilities in L1 in contrast to L2 high achievers.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In other words, the skills one from language are transferred to the other, the person with more L1 practice thus being better at transferring these skills to the other language. They also support Ganschow, Sparks et al's thesis (Ganschow et al, 1992;Sparks et al, 1992;Ganschow, Sparks, & Javorsky, 1998;Sparks, Ganschow, & Javorsky, 2000) that phonological, orthographical, grammatical, and semantic L1 skills form the basis for learning L2. These authors found that students who find learning L2 difficult have low-level learning disabilities in L1 in contrast to L2 high achievers.…”
Section: Discussionsupporting
confidence: 69%
“…These results constitute both a new finding and a significant expansion of the results of previous studies in the field (Ganschow & Sparks, 1996;Ganschow et al, 1994;Ganschow, Sparks, & Javorsky, 1998;Sparks & Ganschow, 1993;Sparks et al, 1992;Sparks, Ganschow, & Javorsky, 1998), which focused on the interaction between an individual's L1 language skills and the level of L2 anxiety. The findings of these studies pointed to variances in the performance of tasks testing spoken language (listening and conversation), phonological processing, orthographic knowledge, and L2 learning aptitude between students exhibiting high and low levels of anxiety.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Dyslexic learners are likely to encounter a large number of problems when learning foreign languages (Downey, Snyder, and Hill 2000;Ganschow, Sparks, and Javorsky 1998;Kormos and Kontra 2008;Sparks et al 2008). Moreover, students with dyslexia often suffer from their environment's reaction to their special situation as well.…”
Section: Background To the Studymentioning
confidence: 99%
“…In many European countries, such assistance has traditionally taken the form of special instruction classes taught by a teacher-therapist or specialist at school or at a psychological-pedagogical clinic. However, in light of general consent among researchers that weak students better be provided with tutoring assistance (Ganschow, Sparks, & Javorsky, 1998;Nijakowska 2008Nijakowska , 2010Sparks, Ganschow, & Patton, 2008;Sparks, Humbach, & Javorsky, 2008) there is an increasing need for research such as this on the effects of training methods and intervention tools that can be used by individuals in their private time.…”
Section: Introductionmentioning
confidence: 99%